2008
DOI: 10.1186/1476-511x-7-14
|View full text |Cite
|
Sign up to set email alerts
|

Raisins and additional walking have distinct effects on plasma lipids and inflammatory cytokines

Abstract: BackgroundRaisins are a significant source of dietary fiber and polyphenols, which may reduce cardiovascular disease (CVD) risk by affecting lipoprotein metabolism and inflammation. Walking represents a low intensity exercise intervention that may also reduce CVD risk. The purpose of this study was to determine the effects of consuming raisins, increasing steps walked, or a combination of these interventions on blood pressure, plasma lipids, glucose, insulin and inflammatory cytokines.ResultsThirty-four men an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 53 publications
4
69
0
2
Order By: Relevance
“…Similar conclusions were reached by Puglisi and coworkers [16] who enrolled 34 men and postmenopausal women in a trial where raisins (1 cup/day) was compared to physical activity (increased number of steps walked) or a combination of two (see Table 1). In fact, there was a significant reduction by 2.2% of systolic pressure in all intervention groups, while diastolic pressure was unchanged.…”
Section: Blood Pressuresupporting
confidence: 63%
See 2 more Smart Citations
“…Similar conclusions were reached by Puglisi and coworkers [16] who enrolled 34 men and postmenopausal women in a trial where raisins (1 cup/day) was compared to physical activity (increased number of steps walked) or a combination of two (see Table 1). In fact, there was a significant reduction by 2.2% of systolic pressure in all intervention groups, while diastolic pressure was unchanged.…”
Section: Blood Pressuresupporting
confidence: 63%
“…Puglisi and co-workers [16] suggested an involvement of the antioxidant properties by raisin polyphenols and the positive modulation of antiinflammatory markers, such as cytokines and TNF-α. Following the protocol described before (see also Table 1), Authors showed a significant modification of some parameters, such as the plasma concentration of sICAM-1 in all intervention trials (raisins, walking or combination of two).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important positive effects reported were: 1) the reduction of systolic blood pressure (5 papers with positive association and one with no significant difference versus control) [9][10][11]; 2) the improvement of endothelial functions, assessed by measuring the flow-mediated-dilatation (FMD) of the brachial artery (11 in favour and 3 without significant results) [9,[12][13][14]. Encouraging results were observed on systolic blood pressure; in fact 5 papers out of 6 indicated a reduction of this parameter in both healthy and pre-hypertensive subjects after the consumption of one cup daily (for 42 days) of raisins or a snack containing raisins 3 times a day (for 84 days) [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…HCD-fed rats were reported to have higher serum lipids levels [29,53], which was in accordance with our findings where HCD-raisins fed rats had a significant decrease in the levels of serum lipids. Puglisi et al [45] found that using one cup of raisins per day for 2 weeks in humans significantly decreased total cholesterol, triglycerides and LDL. This hypolipidaemic effect of raisins might be due to polyphenols content interference with cholesterol absorption [60] and decrease of hepatic cholesterol concentrations as observed in guinea pigs [61] after diet supplementation with lyophilised grape powder.…”
Section: Discussionmentioning
confidence: 99%